2018
DOI: 10.4111/icu.2018.59.6.371
|View full text |Cite
|
Sign up to set email alerts
|

Are there any predictive risk factors for failure of ureteric stent in patients with obstructive urolithiasis with sepsis?

Abstract: PurposeTo compare patients with sepsis due to obstructive urolithiasis (Sep-OU) and underwent drainage by percutaneous nephrostomy (PCN) or a double-J (DJ)-ureteral stent and to identify predictive risk factors of DJ stent failure in these patients.Materials and MethodsWe reviewed our records from January 2013 to July 2018 and identified 286 adult patients with Sep-OU out of which 36 had bilateral involvement, thus total 322 renal units were studied. Urologic residents in training carried out both ureteral ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This reflux might obscure vision during surgery, making it difficult. In clinical practice, patients with urosepsis caused by multiple or larger stones are likely to fail RUS [12]. Wang et al [13] suggested that the primary retrograde approach should be limited to experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…This reflux might obscure vision during surgery, making it difficult. In clinical practice, patients with urosepsis caused by multiple or larger stones are likely to fail RUS [12]. Wang et al [13] suggested that the primary retrograde approach should be limited to experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when ureter stone(s) is large and/or multiple, there is a possibility of ureteral stenting failure. Pandey et al experienced 13.9% of ureteral stenting failure in obstructive stone management [23]. Thus, in cases of ureter stones with intractable pain, we prefer PCN placement rather than double-J stenting.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to compare the effects of each urinary diversion techniques on healthrelated quality of life in patients undergoing onco-gynecology surgery. The previous studies comparing two techniques have evaluated patients with hydronephrosis secondary to ureteral stones or pregnancy [7][8][9]. Most of these studies have investigated the effect of two methods on the improvement of ureteral obstruction and renal function.…”
Section: Discussionmentioning
confidence: 99%